The Antimicrobial Activity of Extracted Shiga Toxin from E. coli O157:H7 on Different Types of Bacteria and Fungi: Aktivitas Antimikroba Toksin Shiga yang Diekstraksi dari E. coli O157:H7 terhadap Berbagai Jenis Bakteri dan Jamur - Khutheir Abbas Ali; Harith Basim Ibrahim Al-Nasiri; Ola Hassan AlSaady (Academia Open, 2026)
General Background: Foodborne pathogens, particularly Escherichia coli O157:H7, remain a major public health concern due to their ability to produce Shiga toxin and their increasing resistance to antimicrobial agents. Knowledge Gap: Limited evidence is available regarding the antimicrobial activity of purified Shiga toxin against diverse bacterial and fungal pathogens isolated from food sources, especially in local contexts. Aims: This study aimed to isolate E. coli O157:H7 from dairy and meat products in Baghdad, purify Shiga toxin, and evaluate its antimicrobial activity against selected bacteria and fungi. Results: Thirty E. coli O157:H7 isolates were obtained from 300 samples. Shiga toxin was successfully purified using ammonium sulfate precipitation and ion-exchange chromatography. The purified toxin showed inhibitory activity against several pathogens, with the lowest minimum inhibitory concentration observed for Candida albicans at 125 µg/mL, while higher concentrations were required for other bacterial species. Novelty: The study demonstrates the selective antimicrobial potential of purified Shiga toxin against both bacterial and fungal pathogens derived from food samples. Implications: These findings provide experimental evidence supporting the potential application of bacterial toxins as alternative antimicrobial agents in food safety and pathogen control strategies. Keywords: Escherichia coli O157:H7, Shiga Toxin, Antimicrobial Activity, Ion-Exchange Chromatography, Foodborne Pathogens Key Findings Highlights: Purified Shiga toxin exhibited selective inhibitory activity against multiple bacterial species and Candida albicans. Meat products showed a higher occurrence of E. coli O157:H7 compared to dairy products in Baghdad markets. Ammonium sulfate precipitation followed by ion-exchange chromatography yielded an active toxin preparation suitable for antimicrobial testing.